Hospital length of stay among children with and without congenital anomalies across 11 European regions—A population-based data linkage study - Urhoj, Stine Kjaer; Tan, Joachim; Morris, Joan K.; Given, Joanne; Astolfi, Gianni; Baldacci, Silvia; Barisic, Ingeborg; Brigden, Joanna; Cavero-Carbonell, Clara; Evans, Hannah; Gissler, Mika; Heino, Anna; et al. (PLOS ONE, 2022)
Background Congenital anomalies are a leading cause of childhood morbidity, but little is known about the long-term outcomes. Objective To quantify the burden of disease in childhood for children with congenital anomalies by assessing the risk of hospitalisation, the number of days spent in hospital and proportion of children with extended stays (≥10 days). Methods European population-based record-linkage study in 11 regions in eight countries including children with congenital anomalies (EUROCAT children) and without congenital anomalies (reference children) living in the same regions. The children were born between 1995 and 2014 and were followed to their tenth birthday or 31/12/2015. European meta-analyses of the outcome measures were performed by two age groups, <1 year and 1–4 years. Results 99,416 EUROCAT children and 2,021,772 reference children were linked to hospital databases. Among EUROCAT children, 85% (95%-CI: 79–90%) were hospitalised in the first year and 56% (95%-CI: 51–61%) at ages 1–4 years, compared to 31% (95%-CI: 26–37%) and 25% (95%-CI: 19–31%) of the reference children. Median length of stay was 2–3 times longer for EUROCAT children in both age groups. The percentages of children with extended stays (≥10 days) in the first year were 24% (95%-CI: 20–29%) for EUROCAT children and 1% (95%-CI: 1–2%) for reference children. The median length of stay varied greatly between congenital anomaly subgroups, with children with gastrointestinal anomalies and congenital heart defects having the longest stays. Conclusions Children with congenital anomalies were more frequently hospitalised and median length of stay was longer. The outlook improves after the first year. Parents of children with congenital anomalies should be informed about the increased hospitalisations required for their child’s care and the impact on family life and siblings, and they should be adequately supported.